Hubungan antara Pendidikan, Agama, dan Ideologi dalam Perspektif Filsafat: Systematic Literature Review - Daniati, Yunita (Yayasan Sembilan Pemuda Indonesia, 2024)
This paper aims to examine the complex relationship between education, religion and ideology through the lens of philosophy. These three concepts of education, religion and ideology have influenced and shaped each other throughout the history of human civilisation. Education is a means of shaping individuals and society, while religion and ideology provide a foundation of values and moral guidance that influence the educational process. From a philosophical perspective, the relationship between education, religion and ideology can be analysed through several questions, including the purpose, meaning and values underlying the education system. These three concepts can be analysed through philosophy, as philosophy is a systematic attempt to understand reality and plays an important role. We can identify various perspectives on how education shapes the character of individuals and society, how religion influences worldview and human behaviour, and how ideology shapes collective identity and political orientation through various schools of philosophy, such as philosophy of education, philosophy of religion, and political philosophy, This research method uses a Systematic Literature Review (SLR) study. The references for this writing come from journals, papers, and articles from 2022 to 2024. The journals, papers and articles reviewed were 15 and came from Google Schoolar. The results of this study are: (1) The relationship between education and Islamic philosophy, (2) The development of philosophy of science in the world of education in Indonesia, (3) The Merdeka curriculum in philosophical review, (4) The relationship between philosophy and religion, law and technology, (5) The relationship between philosophy and the ideology of Pancasila.